Interior defect-induced crack initiation mechanism and initial growth behavior for Ti6Al4V alloy fabricated using laser powder bed fusion - Liu, Fulin (2023)
The interior defect-induced crack initiation mechanism and early growth behavior of Ti6Al4V alloy fabricated by laser powder bed fusion (LPBF) has been investigated in very high cycle fatigue (VHCF) regime. P-S-N curves under 10% and 90% failure probabilities are obtained in VHCF regime. The cracks inside the early stages of fine granular area (FGA) formation are driven by the maximum shear stress and propagate as Mode II + III mixed cracks. It can be found that the FGA region is composed of many discontinuous nanograins for Ti6Al4V alloys manufactured by LPBF, which are responsible for grain refinement. Grain refinement is associated with dislocation movement within the martensite laths. Dislocation pileup and rearrangement in martensitic laths form dislocation cells, which further develop into nanograins and low angle boundaries. Besides, both the fatigue loading process and the LPBF process form their respective microvoids, which merge and aggregate with each other, thus accelerating the microcrack extension.